ANALISIS TEKS SURAT TERHADAP IMPLEMENTASI MERDEKA BELAJAR DALAM KOMPETENSI BERBAHASA SISWA KELAS VII - Farras Al Faathir Nasuton; Fatiyah Salsabilah Lubis; Gracia Lumbantobing; Jesika Margaretha sianipar; Rosmawaty Harahap (STKIP Subang, 2026)
The Independent Curriculum brings fundamental changes in the orientation of Indonesian language learning at the junior high school level from a material-based approach to student-centered learning. Learning personal and official letter texts in Chapter VI of the Indonesian language textbook for grade VII has strategic value as a vehicle for developing comprehensive language competency as well as a real implementation of the principles of Independent Learning. This article aims to describe and analyze the implementation of learning personal and official letter texts in developing Indonesian language competency for grade VII students through a literature study method with the stages of identification, classification, comparison, and synthesis of relevant library sources including Kemendikbudristek regulations, grade VII Indonesian language textbooks, genre-based learning theories, and scientific journal articles on language education. The results of the literature synthesis show that learning letter texts designed based on Phase D Learning Outcomes with a differentiated approach and authentic assessment is proven to be able to respond to the diversity of student learning needs while strengthening the dimensions of the Pancasila Student Profile which include noble character, critical reasoning, and independence. Thus, letter text material is an integral part of developing literate, communicative, and character-based students, in accordance with the ideals of the Independent Curriculum.